Avaliação da imunidade antitetânica em idosos de asilos e grupos de convivência de Belo Horizonte: nível de proteção atual e análise da soroconversão da vacina dupla tipo adulto - Edgar Nunes de Moraes (2002)
The objective of this study was evaluate the protection and serum conversion of tetanus vaccine (as dT) in the elderly from ages homes and seniors centers in Belo Horizonte city, Brazil. This study also evaluated the fidelity of vaccinal history, the serum conversion rate, the factors related to the protective levels of tetanus toxin antibodies and the number of doses of tetanus toxoid needed to achieve immunity. This study began in 1999, after itsapproval by UFMGs Ethical Research Commitee. A sample design was done to collect representative data of old people from two distinct groups: age homes (n=172) and senior centers (n=227), tottaling 399 old persons. The vaccination schedule consisted in three doses of dT vaccine at intervals which varied from 37 to 77 days between the first and second doses and from six to 15 months between second and third doses. The antitoxinantibodies were determinated by the ToBI test and seroprotection was defined as antibody titres equal to or greater than 0,1 UI/mL. The follow up period was 24 months. The logisticregression model was used for assessing the the association between the seroconversion and the other considered variables (sex, age, education, group, malnutrition, vaccination history, degree fo frailty and lethality). To estimate of seroconversion probabilities for eachdose and choice of number of doses were possible by the life table method. No important factor was identified as associated with the protection agains tetanus at usual significance levels (p 0,05). The protection against tetanus was observed in 114 (28,6%) of 399 elders.The probability of immunity against tetanus absence among old people at the initial time was 71,4% (CI 68,3% to 82,8%). The logistical regression analises showed significant association between absence of protection and institucionalization. At about 81,4% of institucionalized elders were not protected against tetaunus while compared with the 68,9% who belonged to senior centers (p=0,001). All the elderly with recent vaccinal history showed protective serum antibody levels. The serum conversion tax among old people from age homes after first, second and third doses of dT was, respectively, 57,85% (CI49%;67%), 85,25% (CI 78%;92%) and 98,23% (CI 95%;100%). For elderly people from seniors centers was, respectively, 72,22% (CI 64%;80%), 87,55 %(CI 81%;94%) and 98,38% (CI 96%;100%). The elderly people from ages homes and seniors centers in BeloHorizonte represent an important group susceptible to tetanus infection. There is no evidence that seroconversion and protection against tetanus are related to the considered covariates, except for institucionalized elderly, whose absence of protection´s risk was significantly greater. This study confirmed de efficacy of dT vaccine in conferring protection against tetanus even in fragile elderly (older than 80 years and completeddependent) and showed that three doses were sufficient to obtain a high level of secure protection against tetanus. The greater susceptibility of elderly to tetanus and the efficacy of the vaccinal schedule are irrefutable arguments that must guarantee the continuance of vaccination against tetanus in the National Immunization Programme in Brazil.